2007
DOI: 10.1590/s1516-635x2007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of the intestinal mucosa of broiler chicks treated with Lactobacillus Spp. and challenged with Salmonella Enteritidis

Abstract: This study aimed at the antibody production by intestinal mucosa of broilers chicks were orally inoculated with Lactobacillus spp. at one and/or 21 days of age, and subsequently challenged with Salmonella enterica, subspecies enterica, serotype Enteritidis (S. Enteritidis). A total number of 288 drug-free broiler chicks was divided into 6 groups (groups A,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Christensen et al, (2002) suggested that some of these effects were mediated by cytokines secreted by immune system cells stimulated with probiotic bacteria. On the other hand, Okamoto et al, (2007) demonstrated that this type of treatment had few beneficial effects for chicks, particularly during the first days of life.…”
Section: Results Listed In Tablementioning
confidence: 99%
“…Christensen et al, (2002) suggested that some of these effects were mediated by cytokines secreted by immune system cells stimulated with probiotic bacteria. On the other hand, Okamoto et al, (2007) demonstrated that this type of treatment had few beneficial effects for chicks, particularly during the first days of life.…”
Section: Results Listed In Tablementioning
confidence: 99%
“…It was centrifuged at 3000 rpm for 10 min and the sediment was diluted with sterile phosphate buffer saline and adjusted to contain 10 9 CFU/mL using a McFerland matching tube to be used for challenging. According to the method of Timms [22], the challenge inoculum was prepared at 28 days of age, each bird in the challenged groups was infected orally with 0.5 mL suspension containing 10 9 CFU/mL SE [23]. The commercial balanced ration that met the broiler chicken requirements according to the National Research Council [24] was used as follows: starter (23% crude protein and metabolizable energy 3008 Kcal/kg), grower (21% crude protein and 3080 Kcal/kg diet) and finisher feed (19% crude protein and 3190 Kcal/kg diet) until 12, 26 and 42 days of age, respectively.…”
Section: The Challenge Bacteriummentioning
confidence: 99%
“…Increasing evidence indicates that Lactobacillus and Pediococcus strains exert beneficial effects by a variety of complementary mechanisms, including an ability to modulate host immune function, high adhesion capacity, cancerpreventing attributes, reduction of serum cholesterol levels, high antimicrobial activity against pathogens, and normalization of the microbiota composition (Okamoto et al, 2007;Noujaim et al, 2009; Isolation and Probiotic Potential of Lactobacillus salivarius and Pediococcus pentosaceus in Specific Pathogen Free Chickens Meng et al, 2010;Zhang et al, 2011;Kiran et al, 2015;Xie et al, 2015;Zhang et al, 2015). Promising probiotic strains should have some superior biological properties, especially improving growth performance, intestinal microbiota balance, and meat quality, and decreasing noxious gas emission (Meng et al, 2010;Fan et al, 2013;Jeong et al, 2014;Peng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%